2017
DOI: 10.4324/9781315561691
|View full text |Cite
|
Sign up to set email alerts
|

Health and Political Engagement

Abstract: Health and Political Engagement Social scientists have only recently begun to explore the link between health and political engagement. Understanding this relationship is vitally important from both a scholarly and a policy-making perspective. This book is the first to offer a comprehensive account of health and political engagement. Using both individual-level and country-level data drawn from the European Social Survey, World Values Survey and new Finnish survey data, it provides an extensive analysis of how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 65 publications
2
46
0
Order By: Relevance
“…While education is generally seen as the primary path through which political efficacy is formed, other studies additionally find that poverty (Marx and Nguyen, 2018a), poor health (Mattila et al, 2017;Shore et al, 2020), unemployment (Marx and Nguyen, 2016;Westholm and Niemi, 1986), or minority ethnic and religious status (Abramson, 1983;Oskooii, 2016;Schwartz, 1973) are all associated with lower political efficacy. There are therefore many other potential sources of low political efficacy that can lead to feelings of political alienation and a withdrawal from political engagement (Almond and Verba, 1963).…”
Section: Political Efficacymentioning
confidence: 99%
“…While education is generally seen as the primary path through which political efficacy is formed, other studies additionally find that poverty (Marx and Nguyen, 2018a), poor health (Mattila et al, 2017;Shore et al, 2020), unemployment (Marx and Nguyen, 2016;Westholm and Niemi, 1986), or minority ethnic and religious status (Abramson, 1983;Oskooii, 2016;Schwartz, 1973) are all associated with lower political efficacy. There are therefore many other potential sources of low political efficacy that can lead to feelings of political alienation and a withdrawal from political engagement (Almond and Verba, 1963).…”
Section: Political Efficacymentioning
confidence: 99%
“…Interestingly, political efficacy research does not consider life quality variables, which is surprising, as their importance is demonstrated for other political behavior outcomes (e.g. Mattila et al, 2017; Zuckerman, 2005), and because the concept is frequently tied to personality or other non-political dispositions (Campbell et al, 1960). This research controls for the effects of four non-political variables related to life quality.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Therefore, one can assume that happier people perceive politics in general (external political efficacy) and their role in the political system in particular (internal political efficacy) more positively than less happy people. Health is also a crucial dimension of life quality, and previous studies showed that it is an important predictor of political sentiments (Mattila et al, 2017). For instance, Mattila and Rapeli (2018) report that people’s health is negatively associated with their level of political trust.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…This literature discusses two different explanations at the individual level: resources and motivation (see, e.g., Wolfinger & Rosenstone ; Franklin ). The former category includes factors like high social status with regard to gender, class, occupation, education, income, knowledge and health (Verba et al ; Söderlund et al ; Mattila et al ). Strong social inclusion is another aspect of this category, and this relates to age, marital status, cohabitation and gainful employment (Stoker & Jennings ; Franklin ).…”
Section: Theoretical Framework: Explaining Turnout In Sámi Electionsmentioning
confidence: 99%